Changes in weight and BMI with first-line doravirine-based therapy. (1st January 2021) - Orkin, Chloe; Elion, Richard; Thompson, Melanie; Rockstroh, Juergen K.; Alvarez Bognar, Fernando; Xu, Zhi J.; Hwang, Carey; Sklar, Peter; Martin, Elizabeth A.
Abstract : Objective: To evaluate changes in weight and BMI in adults with HIV-1 at 1 and 2 years after starting an antiretroviral regimen that included doravirine, ritonavir-boosted darunavir, or efavirenz. Design: Post-hoc analysis of pooled data from three randomized controlled trials. Methods: We evaluated weight change from baseline, weight gain at least 10%, and increase in BMI after 48 and 96 weeks of treatment with doravirine, ritonavir-boosted darunavir, or efavirenz-based regimens. Risk factors for weight gain and metabolic outcomes associated with weight gain were also examined. Results: Mean (and median) weight changes were similar for doravirine [1.7 (1.0) kg] and ritonavir-boosted darunavir [1.4 (0.6) kg] and were lower for efavirenz [0.6 (0.0) kg] at week 48 but were similar across all treatment groups at week 96 [2.4 (1.5), 1.8 (0.7), and 1.6 (1.0) kg, respectively]. No significant differences between treatment groups were found in the proportion of participants with at least 10% weight gain or the proportion with BMI class increase at either time point. Low CD4 + T-cell count and high HIV-1 RNA at baseline were associated with at least 10% weight gain and BMI class increase at both timepoints, but treatment group, age, sex, and race were not. Conclusion: Weight gains over 96 weeks were low in all treatment groups and were similar to the average yearly change in adults without HIV-1. Significant weight gain and BMI class increase were similar across the treatment groups and were predicted by low baseline CD4 + T-cell count and high baseline HIV-1 RNA. Abstract : Supplemental Digital Content is available in the text